EFFECT OF MICROBIALLY TREATED INDUSTRY EFFLUENT ON THE GROWTH OF GREEN GRAM (PHASEOLUS AUREUS-ROXB) - J.MANJUNATHAN; P.M.AYYASAMY; V. KAVIYARASAN (International Journal of Pharma and Bio Sciences, 2011)
Biosurfactant are surface-active substances synthesized by living cells-in the majority of cases by microorganisms. Metallic contaminants in the soil are poisonous and their accumulation in plants and water may be dangerous. Microorganisms are known to absorb; adsorb and accumulate heavy metals and they can be made use of in solving major problems associated with metals. The extensive use of chromium in different industries such as leather, textile, metal electro plating etc has resulted in the discharge of chromium compounds into aquatic system. Among the fungal isolates, Mucor sp. ATS 5 was predominant using inactive cells about 84% chromium was removed, whereas in resting cells it was found to be 79%. In the case of bacterial population, Pseudomonas sp. ATS-08 was predominant about 86% chromium was removed using inactive cells followed by resting cells (75%). Among the actinomycetes isolates, Nocardia sp. ATS-2 was predominant. 90% chromium was removed using inactive cells of Nocardia sp. followed by resting cells (84%). From the above study, it is concluded that the actinomycetes was the best effective followed by bacteria and fungi and could be used for treating industrial effluents having high amount of chromium.